1977
DOI: 10.1080/15421407708084391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alignment of Bubble Domains in Large Pitch Cholesteric Liquid Crystals

Abstract: Based on the naive model, the molecular alignment of the bubble domain in large pitch cholesterics is calculated numerically by using the continuum theory of liquid crystals. It is shown that the bubble domain is surely stable under certain conditions but when the cell thickness is thinner than the critical thickness homeotropic alignment is more favourable. The effects of the electric field on the bubble diameter are also investigated. Obtained results agree well qualitatively with the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We note that the study of axially symmetric cholesteric configurations reported here is not exhaustive. In fact, several other configurations might have been already identified in prior literature [20,[23][24][25][26][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] that we have not explored so far using our 3D imaging experiments and different types of generation (laser realignment, low-frequency electric field, temperature quench with and without temperature gradients). In addition, in future work, studies of mutually linked multi-toron and multihopfion configurations that also belong to this family will be reported [51].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We note that the study of axially symmetric cholesteric configurations reported here is not exhaustive. In fact, several other configurations might have been already identified in prior literature [20,[23][24][25][26][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] that we have not explored so far using our 3D imaging experiments and different types of generation (laser realignment, low-frequency electric field, temperature quench with and without temperature gradients). In addition, in future work, studies of mutually linked multi-toron and multihopfion configurations that also belong to this family will be reported [51].…”
Section: Discussionmentioning
confidence: 95%
“…A large number of localized structures are known to occur spontaneously in confinementfrustrated chiral nematic liquid crystals when perpendicular surface boundary conditions compete with the chiral medium's tendency to twist, giving rise to various linear and axially symmetric structures that locally introduce twisted configurations [20]. Although at least four different types of localized linear structures, the so-called "cholesteric fingers," have been identified and successfully modeled numerically [20][21][22], the axially symmetric twist configurations remain much less understood [23][24][25][26][27][28][29][30][31]. Polarizing optical microscopy (POM) [23][24][25][26][27], historically the most common technique used to study LC textures, often yields similar textural appearance for rather different intricate LC field configurations [28] on account of its lack of 3D resolution [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations